Multiwavelength Thulium-Doped Fiber Laser Using a Micro Fiber-Optic Fabry–Perot Interferometer - Meng Wang; Yijian Huang; Li Yu; Zongpeng Song; Dezhi Liang; Shuangchen Ruan (IEEE Photonics Journal)
A compact, all-fiberized multiwavelength thulium-doped fiber laser based on a micro fiber-optic Fabry–Perot interferometer (FPI) and a nonlinear optical loop mirror (NOLM) has been demonstrated. The FPI with a free spectral range of ∼26 nm was used as an effective wavelength selective filter, which was constructed by splicing a ∼71.4-μm long air-filled hollow-core fiber with single-mode fibers at both ends. An NOLM, served as an amplitude equalizer, was used for stabilizing multiwavelength laser operation. Besides switchable single-wavelength operations (1948.00 and 1972.24 nm), stable dual-wavelength operations (1948.02/1974.25 and 1974.16/1975.30 nm) and triwavelength operation (1947.94/1973.03/1974.14 nm) have been obtained. The optical signal-to-noise ratio of each emission laser line is larger than ∼47 dB.